Dampak Ketidak Aktifan Tiktokshop Bagi UMKM Di Indonesia Terhadap Penjualan Terutama Customkids - Pratiwi Herlina Octaviani; Ageng Saepudin Kanda S (Lembaga Pengembangan Kinerja Dosen, 2024)
With the rapid development of information technology, Tiktokshop has become an increasingly popular e-commerce platform in Indonesia. However, selling on Tiktokshop does not always guarantee success, especially for small and medium enterprises (MSMEs) that focus on selling special products such as CustomKids. This research aims to determine the impact of Tiktokshop's inactivity on sales of MSMEs, especially the custom children's industry in Indonesia. This research analyzes various factors that might influence Tiktokshop's inactivity, such as lack of presence, lack of user interaction and algorithm changes. We also assessed the direct impact of the suspension on sales of CustomKids products, taking into account variables such as decreased sales, decreased market share, and the psychological impact on MSME owners. The results of this research will provide insight to MSME owners, the government and stakeholders to help them develop strategies to advance Tiktokshop activities and increase the competitiveness of MSMEs, with a special focus on CustomKids products. It is hoped that the implications of this research finding will help in decision making to improve the performance of MSMEs in the digital era.